PENGARUH RETURN ON ASSET (ROA) DAN RETURN ON EQUITY (ROE) TERHADAP PERTUMBUHAN LABA PADA PT. JASA MARGA, TBK - Khairunnisa; Wulandari; Rimawan, M. (Jurnal Publikasi Manajemen Informatika, 2025)
Profit growth will certainly simulate the investment provisions of investors or potential investors who have provided capital to the company, as well as creditors who help the company to get loans. This study aims to determine the effect of Return On Asset (ROA) and Return On Equity (ROE) on profit growth at PT. Jasa Marga, Tbk. This research is an associative quantitative study. The instrument used in this study is a list of tables in the form of financial reports consisting of net profit data, asset data and equity data. The population in this study is the financial statements of PT. Jasa Marga, Tbk for 16 years. The sample in this study is the financial statements of PT. Jasa Marga, Tbk from 2014 to 2023. The sampling technique used in this study is purposive sampling. Data collection techniques in this study are documentation and literature studies. The analysis technique uses the classical assumption test, multiple linear regression, multiple correlation coefficient, determination test, t test and f test. The results of the study indicate that Return On Asset (ROA) has a significant partial effect on Profit Growth at PT. Jasa Marga, Tbk while Return On Asset (ROA) has no effect and Return On Asset (ROA) and Return On Equity (ROE) have a significant effect simultaneously on Profit Growth at PT. Jasa Marga, Tbk.